Step 1

Consider the provided information,

y=-11....(1)

x+2y=7....(2)

Use the method of substitution to solve the following system of equations.

Step 2

Now, the value of y in the equation (1) put in the equation (2).

x+2(-11)=7

x=7+22

x=29

Hence.

Therefore, the solution is (29,−11).

Consider the provided information,

y=-11....(1)

x+2y=7....(2)

Use the method of substitution to solve the following system of equations.

Step 2

Now, the value of y in the equation (1) put in the equation (2).

x+2(-11)=7

x=7+22

x=29

Hence.

Therefore, the solution is (29,−11).